Analisis morfologi kalimat Fiil dalam Surah Al-Ikhlāṣ: Pola bentuk dan struktur kata kerja - Rafa'i, Nasruddin (Maliki Interdisciplinary Journal, 2026)
This study examines the morphological structure of verbs (fi‘il) in Surah Al-Ikhlāṣ as a contribution to understanding the linguistic precision of the Qur’an. Despite consisting of only four short verses, the surah contains verbs that play a strategic role in shaping and affirming the concept of divine oneness. Using a descriptive–qualitative approach, this research analyzes the roots, patterns, derivational processes, and semantic implications of the verbs قُلْ, يَلِدْ, يُولَدْ , and يَكُنْ . The verb قُلْ functions as a divine command initiating the declaration of tawḥīd, while يَلِدْ and يُولَدْ form an active–passive pair that strongly negates any biological attributes associated with God. The verb يَكُنْ reinforces the absolute denial of equivalence to God through its morphological structure as a deficient verb (fi‘l nāqiṣ) in the jussive form. The findings demonstrate that these four verbs operate coherently to construct a concise yet powerful theological message. This study contributes to Qur’anic linguistics by offering a focused analysis of verb morphology in a short surah and may serve as a reference for systematic Qur’anic Arabic instruction. Future research may extend the analysis to other short surahs and conduct comparative studies on the morphological and rhetorical functions of Qur’anic verbs.